Surgical outcome in aortopulmonary window beyond the neonatal period. Issue 5 (21st March 2019) - Kumar, Vikas; Singh, Rana S.; Thingnam, Shyam K. S.; Mishra, Anand K.; Jaswal, Vivek
Abstract: Objective: Aortopulmonary window (APW) is a rare congenital cardiac defect accounting for 0.1% to 0.2% of all congenital cardiac defects. We here present the current midterm outcome of surgical repair of APW in patients more than 3 months of age. Methods: The retrospective study was conducted to identify all the patients more than 3 months of age at presentation who underwent surgical repair of APW between June 2010 and August 2018 at our tertiary care institute and their outcome was analyzed. Results: We found 14 patients of APW operated at the age of more than 3 months over a period of 8 years. Mean age of the cohort was 2.29 ± 2.96 years ranging from 3 months to 10 years with 57.14% being males. There were 11 (78.57%) patients with isolated APW and 3 (21.43%) had associated cardiac defects including tetralogy of Fallot (n = 1), ventricular septal defect (n = 1), subaortic membrane causing subaortic stenosis (n = 1), and one had extracardiac malformations. Two patients had type I, nine had type II, and three had type III APW as per Jacobs' classification. The mean size of the defect was 14.14 ± 4.33 mm. Mean duration of mechanical ventilation was 26.91 ± 16.65 hours (range, 12.25‐67 hours). There was one in‐hospital mortality and no late mortality over a mean follow‐up of 3.06 ± 2.19 years. None of the patients required any kind of reintervention. Conclusion: Good results can be obtained even on late presentation with adequate perioperative care of the patients with the reversible pulmonary hypertensive disease.